Impact of sugar‐sweetened beverage taxes on purchases and dietary intake: Systematic review and meta‐analysis. (19th June 2019) - Teng, Andrea M.; Jones, Amanda C.; Mizdrak, Anja; Signal, Louise; Genç, Murat; Wilson, Nick
Summary: The aim was to conduct a systematic review of real‐world sugar‐sweetened beverage (SSB) tax evaluations and examine the overall impact on beverage purchases and dietary intake by meta‐analysis. Medline, EconLit, Google Scholar, and Scopus databases were searched up to June 2018. SSB tax evaluations from any formal jurisdiction from cities to national governments were eligible if there was a comparison between pre–post tax (n = 11) or taxed and untaxed jurisdiction(s) (n = 6). The consumption outcome comprised sales, purchasing, and intake (reported by volume, energy, or frequency). Taxed and untaxed beverage consumption outcomes were examined separately by meta‐analysis with adjustment for the size of each tax. The study was registered at PROSPERO (CRD42018100620). The equivalent of a 10% SSB tax was associated with an average decline in beverage purchases and dietary intake of 10.0% (95% CI: −5.0% to −14.7%, n = 17 studies, 6 jurisdictions) with considerable heterogeneity between results ( I 2 = 97%).The equivalent of a 10% SSB tax was also associated with a nonsignificant 1.9% increase in total untaxed beverage consumption (eg, water) (95% CI: −2.1% to 6.1%, n = 6 studies, 4 jurisdictions). Based on real‐world evaluations, SSB taxes introduced in jurisdictions around the world appear to have been effective in reducing SSB purchases and dietary intake.